ADDIE Model Design Process For 21st Century Teaching and Facilitation Activities (Pdpc) In Nationhood Studies Module - Boyman, Siti Noranizahhafizah; Jamal, Mohamad Basri; Razali, Nur Azah; Aziz, Muhammad Shamsinor Abdul (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to delve into the process of designing the Learning and Facilitation (PdPC) module of the Nationhood Studies course in the 21st Century Learning concept. This course aims to foster the spirit of patriotism and self-esteem among students. Literature studies show that 21st Century education has a positive impact on student attitude, motivation, and mastery of knowledge and is not solely focused on facts and theory. In addition, this educational transformation involving the 21st Century learning process has received parental support. It is arguable that 21st Century learning is a transformation that is being made to renew existing education standards to make the education system more flexible, creative, challenging and more complex. Therefore, the development of this module is essential to achieve that aspiration. To develop a systematic module, this study uses the ADDIE model introduced by Dick & Carry (1996). The process of designing this module is described in detail beginning with the stages of analysis, design, development, implementation and evaluation. The implication of this study is that the PdPC activity module is able to achieve effective learning outcomes and a systematic approach in line with the needs of the Ministry of Education in the Malaysian Education Development Plan 2013-2025.